2008
DOI: 10.1073/pnas.0802993105
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional infrared spectra of isotopically diluted amyloid fibrils from Aβ40

Abstract: The 2D IR spectra of the amide-I vibrations of amyloid fibrils from A␤40 were obtained. The matured fibrils formed from strands having isotopic substitution by 13 CA 18 O at Gly-38, Gly-33, Gly-29, or Ala-21 show vibrational exciton spectra having reduced dimensionality. Indeed, linear chain excitons of amide units are seen, for which the interamide vibrational coupling is measured in fibrils grown from 50% and 5% mixtures of labeled and unlabeled strands. The data prove that the 1D excitons are formed from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
225
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(240 citation statements)
references
References 46 publications
13
225
0
2
Order By: Relevance
“…We found that upon isotope dilution, the frequencies of these 3 residues lie within 5 cm Ϫ1 of each other (1,589-1,594 cm Ϫ1 ), indicating that their local electrostatic environments are comparable. Moreover, the isotope frequencies are higher when diluted, indicating that the coupling between isotope labels causes a negative frequency shift, which is consistent with the negative coupling constants predicted for ␤-sheets in amyloid fibril (12). These results emphasize that the isotope-labeled features that are the focus of this study arise from delocalized vibrational modes that involve the cooperative motions of several labeled amide I groups (18).…”
Section: Shown Insupporting
confidence: 74%
See 1 more Smart Citation
“…We found that upon isotope dilution, the frequencies of these 3 residues lie within 5 cm Ϫ1 of each other (1,589-1,594 cm Ϫ1 ), indicating that their local electrostatic environments are comparable. Moreover, the isotope frequencies are higher when diluted, indicating that the coupling between isotope labels causes a negative frequency shift, which is consistent with the negative coupling constants predicted for ␤-sheets in amyloid fibril (12). These results emphasize that the isotope-labeled features that are the focus of this study arise from delocalized vibrational modes that involve the cooperative motions of several labeled amide I groups (18).…”
Section: Shown Insupporting
confidence: 74%
“…Isotope labeling and IR spectroscopy have been used previously to study amyloids, which have provided insight into general aggregation mechanisms (11,12). Most studies rely on small peptide fragments, which do not necessarily translate into the context of the full protein.…”
mentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Recent evidence supports the view that, at the monomeric level, the ensemble of Aβ is a mixture of multiple, nearly isoenergenic conformational species, in agreement with the energy landscape view of protein dynamics proposed by Frauenfelder and coworkers (22).…”
supporting
confidence: 74%
“…Optical 2D techniques have been successfully used toward the study of fast peptide folding kinetics (32,34), hydrogen bonding dynamics (35), ultrafast chemical exchange (30,31), and energy transport in photosynthetic antennae (36). Very recently, there has been considerable interest in the 2DIR field in studying the structure and formation kinetics of various kinds of amyloid aggregates (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…This labeling tactic has been successfully employed to investigate isolated amide units in different peptides and proteins. [16][17][18] Thus, the aim of this study was to explore the vibrational and conformational changes of the (C13,C12)-oxalate ion, from here on referred to as C13-oxalate. To this end, femtosecond IR transient absorption, ultrafast photon echo, and linear absorption IR spectroscopy were employed.…”
Section: Introductionmentioning
confidence: 99%